Monthly Keetch-Byram Drought Index (KBDI) maps for all Lebanon, links to tif files - George Mitri; Mireille Jazi; David McWethy (PANGAEA, 2017)
Monthly Keetch-Byram Drought Index (KBDI) maps for all Lebanon employing monthly rainfall and temperature data downscaled from global climatic data. Files titled Current_1 throughout Current_12 represent KBDI maps of January throughout December consecutively.